A game theory based land layout optimization of cities using genetic algorithm. Issue 3 (3rd July 2019) - Paritosh, Parth; Kalita, Bhaben; Sharma, Deepak
ABSTRACT: Layout optimization is carried out to achieve the true economic potential of cities by ensuring optimal land usage. This paper presents a novel framework to resolve conflicts between types of land usage while considering the effect of neighboring land plots to generate efficient city layouts. The optimization problem is modeled as a game between land-usage based players, each trying to maximize payoff based on expected layout modifications. It is worth noting that this framework aims to include multi-stakeholder competition, land patch shaping, and neighbor plot effects. A game-theory based approach is coupled with genetic algorithm in which swapping and resizing operators are used to generate a new solution. A parametric study on fitness evaluation of algorithmic output layouts is presented. The presented optimization framework has been implemented on land usage map of Guwahati, a city in north-east India.